A Study of various theories and stages of Child development - Singh, Dr Kuldeep (Innovative Research Thoughts, 2017)
Child development incorporates physical growth as well as intellectual, language, emotional and social development. Whilst these aspects are often considered separately, in reality each influences all of the others. For example, as the brain develops physically, so intellectual abilities increase. This in turn allows a child to explore their social world more fully, develop their emotional responses to it and the language needed to describe it, but in turn, this exploration directly impacts on further physical brain development.